2006
DOI: 10.1183/09031936.06.00108105
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status is related to incidence of asthma and respiratory symptoms in adults

Abstract: The aim of the present study was to assess the association between socio-economic status and impaired respiratory health in a 10-yr follow-up of a population-based postal survey in Northern Sweden.Multiple logistic regression was used to estimate odds ratios in relation to socio-economic class, using age, sex, a family history of asthma, smoking habits, and occupational exposures to dust, gases and fumes as possible confounders.The study comprised 2,341 males and 2,413 females. Cumulative incidences were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
62
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 31 publications
17
62
6
Order By: Relevance
“…In our study, these sectors were associated with cough and wheeze, but not asthma. In line with our findings, another Swedish study published in 2006 [7] showed that manual workers had an increased incidence rate of shortness of breath, wheeze, asthma, and cough. Interestingly, both the Finnish [29] and latter Swedish [7] studies had a longitudinal design, while the present study was cross-sectional which could affect the results; the main findings were similar.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, these sectors were associated with cough and wheeze, but not asthma. In line with our findings, another Swedish study published in 2006 [7] showed that manual workers had an increased incidence rate of shortness of breath, wheeze, asthma, and cough. Interestingly, both the Finnish [29] and latter Swedish [7] studies had a longitudinal design, while the present study was cross-sectional which could affect the results; the main findings were similar.…”
Section: Discussionsupporting
confidence: 93%
“…The strength with our study was the large population-based cohort with a high participation rate resulting in a representative study population. Furthermore, the questionnaire and questions [710,14,16,24,26,28,35] have been used in several studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the social determinants positively related to increased mortality and morbidity from respiratory diseases are: type of occupation 1 , education, income and housing 2 . These determinants have increased the prevalence of respiratory symptoms, as well as the risk of dying from lung disease.…”
Section: Introductionmentioning
confidence: 99%